Role of personality traits for entrepreneurial intentions of young entrepreneurs: A case study of higher education institution - Cao, Yuanyuan; Asad, Muhammad Mujtaba; Wang, Lu; Naz, Aisha; Almusharraf, Norah (Frontiers in Psychology, 2022)
Pakistan being a young country, is struggling to provide employment opportunities. However, entrepreneurship is a perceived strategy for reducing unemployment. The trend of entrepreneurship is also emerging among university students. Thus, the ratio of entrepreneurial intention and start-ups is also increasing among university students and graduates. Therefore, this study aims to examine the role of personality traits in the entrepreneurial intentions of young entrepreneurs. Considering this, qualitative methodology was employed with the case study as the research design. A single case of a university with three different departments was taken. In total, n=9 entrepreneurs were purposely selected from business (n=3), computer science (n=3), and education (n=3) departments. The data were collected using semi-structured interviews and documentary analysis of their ventures and success stories. This study followed research ethics, including volunteer participation, confidentiality, and reciprocity. The collected data were analyzed using interpretative phenomenological analysis. The findings reveal three main themes; the desire to be an entrepreneur, learning attitude, and personality traits are the leading factors in the entrepreneurial intentions of students and graduates. However, within these themes, the effect of personality traits (consistency and determination, discipline and locus of control, and risk-taking and tolerance) is found to lead to entrepreneurial intentions among young entrepreneurs. This study concludes that most entrepreneurs believe that the role of personality traits is evident in entrepreneurial intentions. Moreover, the personality traits are further strengthened with entrepreneurial experience and help continue entrepreneurship.